Review of anti-Trichomonas vaginalis herbs and their therapeutic effects - Fatemeh Zahra Karimi; Mohadese Bakhshi; Salme Dadgar; Nahid Maleki-Saghooni (Mashhad University of Medical Sciences, 2018)
Introduction and Objectives: Trichomonas vaginitis is the most common non-viral disease transmitted through sexual contact. Metronidazole is the most effective medication that has the same adverse effects as other synthetic drugs. Since medicinal plants have less side effects and more popularity among most people, this study was conducted to review the effects of anti-trichomonas vaginalis plants and their therapeutic effects. Materials and Methods: Persian and English databases, including PubMed, Medline, Scopus, Google Scholar, SID, IranMedex, and Magiran were searched for articles published between 1976 and 2017 using keywords such as 'Trichomonas vaginalis', 'complementary therapies' and 'medicinal plants' and their Persian equivalents. All the relevant in vivo and in vitro trials were included in the study. Overall, 120 papers were retrieved, 25 of which were critically reviewed. Results: The articles reviewed in this study showed that some herbal compounds (e.g., Zataria multiflora Boiss, Allium staivum, Lavandula stoechas, Eucalyptus, and Myrtus communis)are effective in inhibiting the growth of Trichomonas vaginalis, but further human studies are needed to apply them to the treatment of Trichomonas vaginitis. Conclusion: In spite of the beneficial effects of medicinal herbs on the treatment of Trichomonas vaginitis, since most of the studies were in vitro, the application of these plants requires more in vivo studies to take an effective step towards recognizing natural, low-cost, low-risk, and more accessible treatments.Therefore, the results of this study should be used with caution.